Christopher Marlowe in Context - Bartels, Emily Carroll; Smith, Emma (Emma Josephine) (Literature in context (Cambridge University Press), 2013)
The most up-to-date contextual guide to Christopher Marlowe's world and the full range of his poetry and drama.